Conocimiento y preparación higiénica de alimentos en madres con menores de 5 años del establecimiento de salud Fernando Lores Iquitos 2023 - Andrade Rodríguez, Adriana María (2024)
The objective was to determine the relationship between knowledge and hygienic food preparation in mothers with children under 5 years of age at the Fernando Lores Health Establishment, Iquitos 2023. The type of research was quantitative, the design used was non-experimental, correlational and transversal, the sample included 103 mothers. The techniques were interview, observation and home visit; The instruments were the knowledge questionnaire on hygienic food preparation with a validity of 98.2% and a reliability of 96.25%, and the hygienic food preparation checklist with a validity of 98.5% and a reliability of 96.25%. of 96.25%. of 96.5%. Results: Regarding knowledge about hygienic food preparation, it was found that 66.0% of mothers had low knowledge, 21.4% had regular knowledge, while only 12.6% had high knowledge. In hygienic food preparation, 32.0% had adequate hygienic preparation, and 68.0% had inadequate hygienic preparation, in which 50.5% of mothers did not use light-colored and clean aprons; 47.6% try foods with their fingers; 47.6% spit when preparing food; 46.6% use a dirty spoon to taste food and 39.8% cough or sneeze when preparing food. Statistical significance was determined (p= 0.001 and X 2 = 86.576; df=2; α = 0.05). Conclusion: There is a significant statistical relationship between knowledge and hygienic food preparation in mothers with children under 5 years of age in the study.